Pengaruh Islamic Public Relation Terhadap Kinerja Pada Karyawan KJKS Mandiri Amanah Surakarta - Ariefin Ariefin; Sumadi Sumadi (ITB AAS INDONESIA Surakarta, 2023)
Relationships between people (human relations) are communication between individuals humanely, namely communication that has entered the psychological stage where communicators require communication to understand each other's thoughts, feelings and can take joint actions. This study aims to find out how to realize Islamic public relations (relationships between communities) at KJKS Mandiri Amanah and the role of Islamic public relations in improving the performance of KJKS Mandiri Amanah. The method used in this research is a qualitative scale field research method, this research is devoted to the type of basic research. The data used is primary data in the form of data recorded at KJKS Mandiri Amanah Surakarta. This research was conducted at KJKS Mandiri Amanah which was carried out between February 2021 and July 2021. This study concludes that in realizing Islamic public relations at KJKS Mandiri Amanah, the leader uses several methods including holding regular meetings at the end of each month in order to create chemistry between parties, build good communication between employees and to customers and the community. general. Regarding the role of Islamic Public Relations in improving the performance of KJKS Mandiri Amanah carried out by the leadership and management, namely by further improving its services and prioritizing the convenience and trust of customers